2011
DOI: 10.2495/mpf110131
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of multiphase flow in a model gearbox

Abstract: This study concerns dynamics of a two-phase flow around a rotating solid body. Under consideration is a model of a gear wheel in a gearbox which rotates and is partially submerged in oil. The flow of interest is complex and involves effects of free surface dynamics, rotation, and formation of bubbles and drops. Occurring flow regimes include laminar, transitional and turbulent. The major focus of the investigation is on details of the developed flow, and the purpose is validation of numerical methods developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 15 publications
2
8
0
Order By: Relevance
“…In between a lubricant foam (air‐lubricant mixture) generates. This foam is also present in the gaps between the teeth as shown experimentally by Chernoray . Figure N shows clearly that when the gears mate, this foam condensates ensuring the separation of the gear flanks through the formation of a lubricant layer.…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…In between a lubricant foam (air‐lubricant mixture) generates. This foam is also present in the gaps between the teeth as shown experimentally by Chernoray . Figure N shows clearly that when the gears mate, this foam condensates ensuring the separation of the gear flanks through the formation of a lubricant layer.…”
Section: Resultsmentioning
confidence: 55%
“…This foam is also present in the gaps between the teeth as shown experimentally by Chernoray. 34 Figure 15N shows clearly that when the gears mate, this foam condensates ensuring the separation of the gear flanks through the formation of a lubricant layer. This is fundamental to reduce the friction coefficient as well as to prevent damaging like wear and scuffing.…”
Section: Automatic Proceduresmentioning
confidence: 99%
“…One may assume that the weakened boundary condition significantly reduces the driving efficiency of the gear compared to a viscous pump of full solid cylinder. This is not the case, as measurements by other authors, like [19] and [20] show that for large speeds, the boundary layer momentum thickness and the driven mass flow does not differ significantly between a gear with teeth and a smooth, solid cylinder which has the same width and diameter as the gear tip diameter. …”
Section: Flash Visualization Of the Typical Boundary Layermentioning
confidence: 60%
“…The authors of [19] used flash flow field visualizations and PIV on a single smooth gear and a mesh gear partially immersed in fluid in a closed large rectangular tank. Apart from the few shown visualizations, the comparison of momentum thickness distributions in the boundary layer around the immersed parts showed that for large Reynolds numbers, the momentum thickness distribution of a gear and a cylinder do not differ significantly.…”
mentioning
confidence: 99%
“…The reduction of the power loss can be explained looking at the way in which, with the lower static pressure, the air pillow (Figure ) that takes place around the submerged portion of the gear completely covers the teeth while for the environment pressure condition, air is trapped only in the bottom of the teeth gaps and the teeth tips interact with the lubricant (higher viscosity and density and consequent pressure peaks) causing the higher power dissipation. In dip‐lubrication, in fact, the loss is significantly dependent from the distribution of the contact areas between teeth and the lubricant …”
Section: Resultsmentioning
confidence: 99%